Determinants of financial leverage in oil and gas listed firms: evidence from Malaysia - Norfaiqah Husin,; Saizal Pinjaman, (Penerbit Universiti Kebangsaan Malaysia, 2024)
This paper aims to investigate the influence of firm’s characteristics, namely profitability, firm size, asset tangibility, and liquidity, as well as oil price, on the financial leverage of oil and gas listed firms. This study utilises a quantile regression panel data model to analyse 100 observations in the 25th, 50th (median), and 75th percentiles. Data is sourced from Bursa Malaysia over 2012-2021. Three explanatory variables demonstrated their relationship to financial leverage with consistent significance in each percentile, namely profitability, firm size, and liquidity. Firms with higher profits and liquidity have low debts as they use retained earnings and liquid assets for their financial obligations. In addition, bigger firms have larger debts due to their capacity to meet interest obligations. Meanwhile, other variables show inconsistent significance where the asset tangibility is significant in the 25th and 75th percentiles, while the oil price is only significant in the 75th percentile. The approach utilised provides insights into the varying degrees of impact and significance across percentiles. The findings can assist managerial decision-making in determining the optimal debt level for firms’ operations while mitigating financial risk. The results also act as a source of reference for policymakers in developing effective policies to stabilise the financial leverage of the oil and gas industry by addressing the volatile nature of firm characteristics and oil prices.